A consensus approach for economic dispatch problem in a microgrid with random delay effects. (June 2020) - Yu, Mei; Song, Chao; Feng, Shixian; Tan, Wen
Highlights: Random delays are considered, which is more practical. The delay bounds are calcullated. The algorithm is distributed. Abstract: In this paper, we propose a consensus approach to solve the economic dispatch problem (EDP) with the effect of random delay. The algorithm is distributed and the supply-demand balance is always satisfied. The impact of random time delay on the stability of the algorithm is investigated. Furthermore, one allowable delay bound is calculated based on the Lyapunov stability condition. Some cases are presented to verify the effectiveness of the proposed scheme.